Analisis Geomorfologi dan Oseanografi untuk Identifikasi Tipologi Pulau Kecil: Studi Kasus di Kepulauan Maluku Utara dan Karimunjawa - Bachtiar Wahyu Mutaqin; Diki A. Amanatulloh; Taufik Budi Waskita; Muh Aris Marfai; Muhammad Nadafa Isnain; Mulyadi Alwi; M. Rokhis Khomarudin (Universitas Lambung Mangkurat, 2022)
AbstractSmall islands in Indonesia have a vital role in developing social, economic, cultural, environmental, and national sovereignty. On the other hand, small islands are also very vulnerable to natural disasters and dynamics and/or human activities. Threats and disasters that exist on small islands can vary according to the characteristics and typology of the island. This study aims to identify the typology of small islands by utilizing geospatial data to analyze geomorphological parameters, including morphology, materials, processes, and oceanographic parameters such as the presence of coral reef ecosystems. The method in this research is divided into three stages, namely pre-field, field measurement, and post-field. Pre-field activities include formulating the characteristics of each island typology through literature studies and geospatial processing data, such as DEM and SPOT 7 satellite imagery, for the preparation of thematic maps. The field stage includes terrestrial surveys in the form of aerial photography, profiling, validation of interpretation results, and diving. The post-field step is carried out to process and analyze the results of the terrestrial survey conducted at the field stage. The analysis was carried out descriptively based on the results of data processing to determine the typology of the islands studied in this research case study. Based on the parameters that have been set and the results of field measurements, the islands of Mare and Tidore in the North Maluku Islands and Karimunjawa and Kemujan islands in the Karimunjawa Islands are categorized as small volcanic islands. Meanwhile, Cemara Besar Island in the Karimunjawa Islands is a small atoll island. Threats to small volcanic islands can be in the form of geological disasters such as earthquakes, volcanic eruptions, and tsunamis. On small atoll islands, the threat that lurks is related to the lack of freshwater and the physical-morphological dynamics of the island, which is strongly controlled by hydro-oceanographic characteristics.Keywords: geospatial, small volcanic island, small atoll island, morphology, disaster. AbstrakPulau-pulau kecil di Indonesia memiliki peranan vital dalam pengembangan sosial, ekonomi, budaya, lingkungan, dan kedaulatan bangsa. Di sisi lain, pulau kecil juga sangat rentan terhadap bencana maupun perubahan alam dan/atau aktivitas manusia. Ancaman dan bencana yang ada di pulau kecil dapat berbeda-beda mengikuti karakteristik dan tipologi pulau tersebut. Penelitian ini bertujuan untuk melakukan identifikasi tipologi pulau kecil dengan memanfaatkan data geospasial dalam analisis parameter geomorfologi yang meliputi morfologi, material, proses, serta parameter oseanografi seperti keberadaan ekosistem terumbu karang. Metode dalam penelitian ini dibagi menjadi tiga tahapan, yaitu pra lapangan, pengukuran lapangan, dan pasca lapangan. Kegiatan pra lapangan meliputi perumusan karaketristik masing-masing tipologi pulau melalui studi literatur serta pengolahan data geospasial, seperti DEM dan citra satelit SPOT 7, untuk penyusunan peta tematik. Tahap lapangan meliputi survei terestris berupa pengambilan foto udara, profiling, validasi hasil interpretasi, dan penyelaman. Tahap pasca-lapangan dilakukan untuk mengolah dan menganalisis hasil survei terestris yang dilakukan pada tahap lapangan. Analisis dilakukan secara deskriptif berdasarkan hasil pengolahan data untuk menentukan tipologi pulau-pulau yang dikaji dalam studi kasus penelitian ini. Berdasarkan pada parameter yang telah ditetapkan dan hasil pengukuran lapangan, maka Pulau Mare dan Tidore di Kepulauan Maluku Utara serta Pulau Karimunjawa dan Kemujan di Kepulauan Karimunjawa dikategorikan sebagai pulau kecil vulkan. Sedangkan Pulau Cemara Besar di Kepulauan Karimunjawa merupakan pulau kecil atol. Ancaman bagi pulau kecil vulkan dapat berupa bencana geologi seperi gempabumi, erupsi gunungapi, dan tsunami. Pada pulau kecil atol, ancaman yang mengintai berkaitan dengan minimnya sumberdaya air tawar dan dinamika fisik-morfologi pulau yang sangat dikontrol oleh karakteristik hidro-oseanografi.Kata kunci: geospasial, pulau kecil vulkan, pulau kecil atol, morfologi, kebencanaan.